Designing New Methodologies for Integrating Biomedical Information in Clinical Trials - Maojo, V.; García-Remesal, M.; Billhardt, H.; Alonso-Calvo, R.; Pérez-Rey, D.; Martín-Sánchez, F. (Methods of Information in Medicine, 2006)
Objectives: To propose a modification to current methodologies for clinical trials, improving data collection and cost-efficiency. To describe a system to integrate distributed and heterogeneous medical and genetic databases for improving information access, retrieval and analysis of biomedical information.Methods: Data for clinical trials can be collected from remote, distributed and heterogeneous data sources.In this distributed scenario, we propose an ontology-based approach, with two basic operations: mapping and unification. Mapping outputs the semantic model of a virtual repository with the information model of a specific database. Unification provides a single schema for two or more previously available virtual repositories. In both processes, domain ontologies can improve other traditional approaches.Results: Private clinical databases and public genomic and disease databases (e.g., OMIM, Prosite and others) were integrated. We successfully tested the system using thirteen databases containing clinical and biological information and biomedical vocabularies.Conclusions: We present a domain-independent approach to biomedical database integration, used in this paper as a reference for the design of future models of clinico-genomic trials where information will be integrated, retrieved and analyzed. Such an approach to biomedical data integration has been one of the goals of the IST INFOBIOMED Network of Excellence in Biomedical Informatics, funded by the European Commission, and the new ACGT (Advanced Clinico-Genomic Trials on Cancer) project, where the authors will apply these methods to research experiments.
Keywords: Database integration; clinical trials; ontologies; biomedical informatics; genomic medicine